2018
DOI: 10.1016/j.procbio.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of carbamazepine by laccase-mediator system: Kinetics, by-products and toxicity assessment

Abstract: A B S T R A C TCarbamazepine (CBZ) is one of the most detected pharmaceutical compounds around the world, with adverse human and animal health impacts in wastewater effluents. Recently, biocatalytic degradation using ligninolytic enzymes such as laccase along with redox mediators provides a promising approach for their removal from water and wastewater. However, the effects of operational parameters on biotransformation need to be investigated in order to design a robust and efficient process. In this research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…The products after CBZ interaction with native HRP-and LiP enzymes are presented in Figure S6a-c respectively. A detailed mass-spectrometric investigation on the products for CBZ (Scheme 3, compound a) transformation by laccase is given in [48]. The two main products detected were: 10,11-dihydro-10,11-dihydroxy-CBZ (DiOH-CBZ) (Scheme 3, compound b) and 10,11-dihydro-10,11-epoxy-CBZ (EP-CBZ) (compound c).…”
Section: Degradation Of Carbamazepine By Non-immobilized Enzymesmentioning
confidence: 99%
“…The products after CBZ interaction with native HRP-and LiP enzymes are presented in Figure S6a-c respectively. A detailed mass-spectrometric investigation on the products for CBZ (Scheme 3, compound a) transformation by laccase is given in [48]. The two main products detected were: 10,11-dihydro-10,11-dihydroxy-CBZ (DiOH-CBZ) (Scheme 3, compound b) and 10,11-dihydro-10,11-epoxy-CBZ (EP-CBZ) (compound c).…”
Section: Degradation Of Carbamazepine By Non-immobilized Enzymesmentioning
confidence: 99%
“…Moreover, recent evidence suggests that reaction conditions could play a determinant role in CBZ degradation. Naghdi et al [57] observed that addition of ABTS increased degradation of CBZ from 30% to 82% in 24 h by a laccase extract from T. versicolor, but when reaction conditions were optimized to 35 °C, pH 6, with 60 U L -1 of enzyme 25 concentration and 18 μM of mediator up to 95% removal was obtained. Further investigation should be done in order to find the conditions allowing CBZ degradation in the matrix.…”
Section: Effect Of Syringaldehyde Additionmentioning
confidence: 99%
“…This result highlights the potential in further applying lignin-degrading systems to nylon biodegradation. The use of laccase-mediator systems has since not focused on plastic, but on bioremediation of other compounds such as perfluoroctanesulfonate, carbamazepine, and non-steroidal antiinflammatory drugs (NSAIDs) (Luo et al, 2018;Naghdi et al, 2018;Apriceno et al, 2019).…”
Section: Naturally Occurring Activity From Enzymes That Degrade Naturmentioning
confidence: 99%